The mediating role of subjective social status in the association between objective socioeconomic status and mental health status: evidence from Iranian national data - Nasirpour, Nastaran; Jafari, Kasra; Habibi Asgarabad, Mojtaba; Salehi, Masoud; Amin-Esmaeili, Masoumeh; Rahimi-Movaghar, Afarin; Motevalian, Seyed Abbas (Frontiers in Psychiatry, 2024)
Introduction Low socioeconomic status (SES) is identified as a pivotal risk factor for mental health. Objective socioeconomic status (OSS) is measured by tangible resources, whereas subjective social status (SSS) reflects an individual’s perception of their OSS. A paucity of literature exists that elucidates the specific psychosocial mechanisms or pathways linking OSS with mental illness via SSS. This research aimed to explore the mediating role of SSS in the OSS-mental health association, utilizing data from the Iranian Mental Health Survey (IranMHS). Methods This study is a secondary analysis of data from IranMHS, a national survey conducted in 2011 through face-to-face interviews with 7,886 Iranian adults aged 15-64. As part of the original survey, the General Health Questionnaire-28 (GHQ-28) was randomly administered to half of these participants. We focused our analysis on data from 3,759 participants who completed all items of the GHQ-28. OSS was evaluated using education, occupation, wealth, and a combined OSS index, while SSS was measured using the MacArthur Scale. We examined how SSS mediates the associations between OSS factors and GHQ scores, including its four dimensions—somatic symptoms, anxiety and insomnia, social dysfunction, and severe depression— while adjusting for demographic variables and conducting gender-stratified analyses. Results Among the 3759 respondents, 2157 (57.4%) were women, 2110 (56.1%) lived in urban areas, with an average age of 33.1 years (SD=12.1). SSS mediated the associations between wealth and the overall GHQ score (mediation percentage: 92.3%), education (75.4%), OSS index (66.7%), and occupation (34.0%) on the GHQ score. The most significant mediation effects were observed for wealth on the somatic symptoms, social dysfunction, and depression dimensions, with SSS accounting for more than 80% of these associations. Conclusion The findings indicate a significant mediating role of SSS in the relationship between OSS and mental health. Enhancing our comprehension of the social determinants that moderate the relationship between objective and subjective socioeconomic status may contribute to a more nuanced understanding of the impact of SES on mental health outcomes.